Stressful Life Events and Chronic Fatigue Among Chinese Government Employees: A Population-Based Cohort Study - Qiu, Dan; He, Jun; Li, Yilu; Li, Ruiqi; Ouyang, Feiyun; Li, Ling; Luo, Dan; Xiao, Shuiyuan (Frontiers in Public Health, 2022)
Background Currently, evidence on the role of stressful life events in fatigue among the Chinese working adults is lacking. This study aimed at exploring the prospective associations between stressful life events and chronic fatigue among Chinese government employees. Methods From January 2018 to December 2019, a total of 16206 government employees were included at baseline and they were followed-up until May 2021. A digital self-reported questionnaire platform was established to collect information on participants’ health and covariates. Life events were assessed by the Life Events Scale (LES), fatigue was assessed by using a single item, measuring the frequency of its occurrence. Binary logistic regression analysis was used for the data analysis. Results Of the included 16206 Chinese government employees at baseline, 60.45% reported that they experienced negative stressful life events and 43.87% reported that they experienced positive stressful life events over the past year. Fatigue was reported by 7.74% of the sample at baseline and 8.19% at follow-up. Cumulative number of life events at baseline, and cumulative life events severity score at baseline were positively associated with self-reported fatigue at follow up, respectively. After adjusting sociodemographic factors, occupational factors and health behavior related factors, negative life events at baseline (OR: 2.06, 95% CI: 1.69 - 2.51) were significantly associated with self-reported fatigue at follow-up. Some specific life events including events related to work and events related to economic problems were significantly associated with self-reported fatigue. Specifically, work stress (OR=1.76, 95%CI: 1.45 - 2.13), as well as not satisfied with the current job (OR=1.95, 95%CI: 1.58 - 2.40), in debt (OR=1.75, 95%CI: 1.40 - 2.17) were significantly associated with self-reported fatigue. The economic situation has improved significantly (OR=0.62, 95%CI: 0.46 - 0.85) at baseline was significantly associated with lower incidence of self-reported fatigue. Conclusion Negative stressful life events were associated with fatigue among Chinese government employees. Effective interventions should be provided to employees who have experienced negative stressful life events.